Watson Health vs Google Health: A Comparative Analysis of AI in Digital Health - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2023)
Watson Health vs Google Health: A Comparative Analysis of AI in Digital Health The integration of Artificial Intelligence (AI) into healthcare has long ...
Keywords: Drug Discovery; Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation